A reversible and highly selective two-photon fluorescent "on–off–on" probe for biological Cu2+ detection. Issue 13 (13th March 2018) - Wang, Hui; Fang, Bin; Zhou, Le; Li, Di; Kong, Lin; Uvdal, Kajsa; Hu, Zhangjun
Abstract : L was used to track Cu 2+ in the cellular endoplasmic reticulum using two-photon microscopy. Abstract : A two-photon active probe for physiological copper (Cu 2+ ) detection is expected to play an important role in monitoring biological metabolism. Herein, a novel Schiff base derivative ( E )-2, 2′-((4-((4-(diethylamino)-2-hydroxybenzylidene)amino)phenyl)azanediyl)bis(ethan-1-ol) (L ) with remarkable two-photon activity was developed and synthetically investigated.L presents high selectivity and sensitivity for Cu 2+ sensing in ethanol/HEPES buffer (v/v, 1 : 1), which is accompanied by the fluorescence switching "off" and subsequently "on" with the addition of EDTA. The mechanism for the detection of Cu 2+ is further analyzed using 1 H NMR titration, mass spectra and theoretical calculations. Furthermore, since the probeL possesses good photophysical properties, excellent biocompatibility and low cytotoxicity, it is successfully applied to track Cu 2+ in the cellular endoplasmic reticulum by two-photon fluorescence imaging, showing its potential value for practical applications in biological systems.